Multimedia Flash Basic Mathematic Learning for Primary School - Tiurma Manurung, Rosida; Amalia, Ainna; Vega Vitianingsih, Anik; Rizky, Swaditya; Susanto, Eko (International Journal of Engineering and Technology, 2018)
The development of education world at this time no doubt has entered a new era, namely the era of global economy, and the era of science and information in various fields including in the field of education that gave birth to the concept of e-learning. The learning process is the result of the synergy of the three main components of learning, namely learners, teacher competence, and learning facilities and from these three components then the learning of mathematics algebra will be more meaningful and appealing to students if teachers can convey and present issues more easily understood and close to the daily life of students by providing material in the form of animated multimedia designed using Adobe Flash CS6.Â Â